MMPI and HAD scale comparison - Bunevičius, R.; Žilėnienė, S. (Psichologija, 1991)
An effort was made to compare HAD scale (Hospital Anxiety and Depression Scale) by Zigmond A. S. and Snaith R. R. and MMPI (Minnesota Multiphasic Personality Inventory) on a sample of 54 female· patients, hospitalised in somatic (59,3 %) and psychiatric (40,7 %) departments. The HAD scale was found to have a relatively high correlation with MMPI clinical scales of depression, psychastenia and Taylor anxiety scale (ranging from 0,61 to 0,63), and can be compared.
Keywords: MMPI; HAD; testing